ANALISIS CORPORATE SOCIAL RESPONSIBILITY, PROFITABILITAS, UKURAN PERUSAHAAN, DAN LEVERAGE TERHADAP AGRESIVITAS PAJAK (Studi Empiris Perusahaan Manufaktur yang Listing di Bursa Efek Indonesia PeriodeTahun 2015 – 2017) - Sulistyoningrum, Ratna (Universitas Slamet Riyadi, 2019)
This study aims to examine the effect of CSR, profitability, company size and leverage against the tax aggressiveness of the manufacturing company listed on the Indonesia stock exchange in the period from 2015 to 2017. The population in this research is all manufacturing companies which amounted to 150 companies. Samples taken based on criteria and obtained 51 companies, so the samples research amounted 153 research data. The data analysis techniques is, descriptive test, classic assumption test, multiple linear regression, and hypothesis test. Based on the result of first hypothesis is negative relationship and not significant. The second is a negative relationship and significant. The third is a positive relationship and not significant. The fourth is a positive relationship and not significant effect against tax aggressiveness.